Cultural and Ekistic Heritage of Princes’ Islands: A Study on Halki and Its Enhancement Through Augmented Reality - Anna Chatsiopoulou; Vasilis Dimitriadis; Maria Panakaki; Eleni G. Gavra; Nikolaos Liazos; Panagiotis D. Michailidis (Heritage)
This study aims to photograph, design, and digitally document the surviving residential buildings on the island of Halki (Heybeliada), within the Princes’ Islands. This documentation focuses on the architectural, urban, and historical aspects of Halki, highlighting the significant material evidence of the Greek social and economic presence. It also examines the urban cultural heritage as depicted in Turkish literature of that period to understand how Turkish writers perceived and presented Halki, referencing the Princes’ Islands only for background context. The methodology includes the collection of material from residents through bibliographic and field research conducted on Halki. Based on these findings, a mobile augmented reality (AR) application was developed using the TaleBlazer platform, designed specifically for use on Halki. The application provides a virtual tour with multimedia-supported thematic layers of architectural and historical information. Its usability and learnability were evaluated using a questionnaire completed by students. The results showed high usability, user satisfaction, and perceived value of learning, with the majority of results close to a median score of 4 out of 5. The students identified the occurrence of immersive experience, ease of use, and the emotional stimulation created by the integration of spatial storytelling and multimedia. This paper also shows how the convergence of cultural content (history, architecture, and literature) can enhance interpretations and experiences with mobile AR technologies.